Pelaksanaan Program Badan Usaha Milik Desa (BUMDes) Di Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - M Muslih; Masriyani Masriyani; Ryanda Putra Pratama (Universitas Batanghari Jambi, 2020)
To carry out national development in the smallest area unit called the Village, an effort is needed to achieve the welfare of the Village community by exploring the existing Village Original Opinion sources (PADes). One form of the source of PADes is derived from the profits generated by the Village-Owned Enterprises. Villages can establish village-owned enterprises called BUMDes. It aims to make the village community able to develop assets owned by the village to become one of the sources of the PADes. The implementation of BUMDes activities in the Jambi Luar Kota sub-district became a research in writing this thesis with a focus on the problem of the implementation of BUMDes activities in several villages in the Jambi Luar Kota sub-district namely Sungai Duren Village, Mendalo Laut Village and Senaung Village based on Village Minister Regulation Number 4 of 2015 and factors inhibitors in BUMDes activities in Jambi Luar Kota sub-district. The research method used is empirical juridical, data analysis derived from interviews with respondents / resource persons related to BUMDes activities in Jambi Luar Kota District. So the results of this study will focus on the implementation of BUMDes activities in the Jambi Luar Kota sub-district.